Viloncello Classics : A Collection Of Original Pieces And Arrangements For Violoncello, With Accompaniment Of Piano - Schulz, Leo (G. Schirmer Inc., 1900)
Sarabande And Gavotte, Romance Sans Paroles, Herbstblume, Kol Nidrei